Monitoring of a NFT-scale hydroponic system using arduino architecture (PART 1) - Urdiales-Ponce, Víctor (2018)
This is why an alternative for the monitoring of essential variables within a field (temperature and pH) is presented. For this, a low-cost hydroponic plantation was used, which served as a prototype of the study, using ARDUINO programming cards for acquisition Of data, in order to monitor the behavior of the variables mentioned above. The information acquired comes from sensors, which generate signals that go to the inputs of the Arduino card.The design is based on a monitoring system, which uses a code developed in Arduino platform, which reads measurements taken from temperature and pH sensors, which are displayed on a led screen to monitor existing conditions In the cultive.